Understanding Individual Differences in English Learning Motivation - Nurisma Ilfidzatur Ridza; Tiyas Saputri; Nailul Authar; Novi Rahmania Aquariza (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Motivation in English learning plays a crucial role in determining students’ achievement and long-term engagement with the language. Students who are highly motivated tend to participate actively in learning activities, practice language skills more frequently, and demonstrate greater persistence when facing challenges. This study aims to explore the factors that influence motivation in English learning through a conceptual approach based on the synthesis of relevant literature. The study integrates major motivational frameworks, particularly Self-Determination Theory and Social Cognitive Theory, to explain how motivation develops and is maintained in educational settings. Findings from the reviewed literature indicate that motivation is influenced by multiple interconnected factors, including individual learning styles, self-efficacy, personal goals, emotional conditions, social support, teacher-student relationships, and cultural perceptions toward English. In addition, the learning environment plays a significant role in fostering or hindering students’ willingness to learn. Supportive classroom practices, meaningful learning activities, constructive feedback, and opportunities for autonomy are consistently associated with higher levels of motivation. Based on these findings, a theoretical model is proposed to illustrate the dynamic interaction between personal, social, and environmental factors in shaping students’ motivation. The model highlights the importance of designing adaptive and learner-centered educational experiences that accommodate diverse student needs, interests, and backgrounds. By understanding the complex nature of motivation, educators can implement more effective instructional strategies that encourage sustained engagement and language development.